Strategi membangun identitas bangsa melalui pendidikan karakter berbasis Pancasila di era multikultural global - Agus, Andi Aco (Research Agency for Humanity and Urban, 2025)
This study aims to determine the concept of Pancasila-based character education as a pillar of national identity, strategies for implementing Pancasila-based character education, challenges in implementing character education in the global era, as well as solutions and steps to strengthen national identity. The research method used is descriptive research with a literature review (library research). The research activities were carried out by collecting information and data with the help of various available materials. The results of the study show that Pancasila-based character education is very relevant in a multicultural context. The values of tolerance, unity, and deliberation taught in Pancasila can be used as a foundation for maintaining diversity. Indonesian national identity is not only determined by one culture, but by a mutual agreement to live based on Pancasila values. Within this framework, character education can be directed towards fostering a sense of pride in diversity while strengthening a sense of unity. Thus, national identity is not only understood symbolically, but also manifested in everyday attitudes and behaviors in society. The strategy for implementing Pancasila-based character education is curriculum integration, whereby Pancasila values must be incorporated into subjects and everyday educational practices.